An analysis of the readability of selected passages from Macbeth and The merchant of Venice with a view to suggesting a framework for a teaching strategy for second language learners studying Shakespearian drama at secondary school level - Meyer, N. A (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ed.) -- University of Stellenbosch, 1985.